Alloying effect on the lattice thermal conductivity of MNiSn half-Heusler alloys. Issue 1 (8th December 2022) - Rabin, Daniel; Fuks, David; Gelbstein, Yaniv
Abstract : The lattice thermal conductivity of MNiSn (M = Ti, Zr, Hf) half-Heusler (HH) alloys was studied. Abstract : The lattice thermal conductivity of MNiSn (M = Ti, Zr, Hf) half-Heusler (HH) alloys was studied. Ab initio DFT calculations were used for the calculation of the material physical properties. A combination of the Slack model and Klemens analytical alloying model was used to simulate the lattice thermal conductivity as a function of composition and temperature. Our results emphasize the major role of point defect scattering in a single-phase state of HH alloys because of the mixing of elements in the M-sub-lattice, especially at the high working temperature of the thermoelectric material. We performed a series of calculations from pure unalloyed compounds to multicomponent compositions with five elements in the M sub-lattice of (Ti, Zr, Hf, Al, Sc)NiSn.